Human ICT Implants: Technical, Legal and Ethical Considerations
XXII, 186 p.
Keywords: With a Foreword by Professor Rafael Capurro, International Centre for Information Ethics (ICIE); Distinguished Researcher in Information Ethics, School of Information Studies, University of Wisconsin-Milwaukee, USA Considered by many to be science fiction, information and communication technology (ICT) has been implanted into the human body for years. Medical human ICT implants such as cochlear implants are in common use, forming intimate links between technology and body. Such restorative devices are increasingly advanced, with some directly interacting with the brain and others near outperforming their natural counterpart. Recently, low-tech human ICT implants have been increasingly employed in non-therapeutic contexts. Applications include VIP nightclub entry, automated payments and controlling secure access. With self-experimenters pushing boundaries and medical technology drift to non-medical application, this is clearly just the beginning. Opportunities for human enhancement through ICT implants have become very real. Despite stakeholders calling for greater legal certainty, gaps have already emerged between the commercial reality of human ICT implants and the legal frameworks used to regulate them. It is not surprising that increasing commercialisation and growing potential has generated debate over the ethical, legal and social aspects of the technology, its products and application. And its trajectory. The contributors to this book, all leaders in their respective fields, not only focus on the latest technological developments, but also the legal, social and ethical implications of the use and further application of these technologies. .